Pelatihan Strategi Bisnis UMKM Bengkulu Menggunakan Media Sosial - Oktaria, Sheren Dwi; Saputri, Rima Yuni (Yayasan Darussalam Bengkulu, 2023)
In today's digital era, social media is considered the right platform for selling and promoting MSME products. The purpose of this Community Service is to provide strategic training. The community service method for MSMEs in Bengkulu includes training that uses a discussion and socialization approach. This business strategy training with social media can help MSMEs improve their marketing performance and encourage business growth in the digital era. Providing business entrepreneurship training using social media can also benefit small businesses by increasing revenue, increasing brand awareness, improving networking capabilities, following industry trends, and making informed decisions. Business strategies using social media into business entrepreneurship training are strategic decisions that can have many benefits for small businesses. MSMEs can also develop an opportunity-centered entrepreneurial mindset, where MSMEs learn to identify and capitalize on opportunities, think creatively, and take calculated risks.